Social Polarization and Partisan Voting in Representative Democracies - Dominik Duell; Justin Mattias Valasek (Center for Economic Studies and ifo Institute (CESifo), 2018)
While scholars and pundits alike have expressed concern regarding increasing social polarization based on partisan identity, there has been little analysis of how social polarization impacts voting. In this paper, we incorporate social identity into a principal-agent model of political representation and characterize the influence of social polarization on partisan voting. We show that social identity has an indirect effect on voting through voters' beliefs regarding the ex post decision of political representatives on top of a direct effect through an expressive channel. We conduct a laboratory experiment designed to identify the relative effect of the two channels. We find that social polarization causes partisan voting, and that up to fifty-five percent of partisan voting is due to the indirect effect of social identity.
Keywords: D72; 330; social identity; partisan voting; social polarization; political polarization